PENGARUH PEMBERIAN DOSIS PUPUK ANORGANIK TUNGGAL N,P,K DAN JENIS PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays subsp. mays L.) - Muhamad Akbar Amanda; Sri Ritawati; Nur Iman Muztahidin; Dewi Firnia (Agros Journal of Agriculture Science, 2023)
This study aimed to determine the effect of single dose of inorganic fertilizer N,P,K and the type of biological fertilizer on the growth and yield of sweet corn (Zea mays subsp. mays L.). The study was arranged in a randomized block design (RBD) with two factors. The first factor was the dose of single inorganic fertilizer N,P,K, which consisted of 3 levels: D1: 100%, D2: 75%, and D3: 50%. The second factor is the type of biological fertilizer, which consisted of 3 levels: P1: Sinarbio, P2: Kayabio, and P3: Ecofert. The results showed that the application of a single inorganic fertilizer N,P,K at a dose of 75% had a significant effect on the parameters of plant height, number of leaves, stem diameter, number of cobs planted, cob weight with cornhusk, cob weight without cornhusk, and yield potential. The type of biofertilizer Sinarbio has a significant effect on the parameters of plant height, number of leaves, stem diameter, number of cobs planted, number of cobs per plot, cob weight with cornhusk, cob weight without cornhusk, and yield potential. The use of a single dose of inorganic fertilizer N,P,K can be reduced to a dose of 75% of the recommendation for sweet corn plants with the application of biofertilizer Sinarbio.